Peran Mediator dalam Mediasi Sengketa Waris di Pengadilan Agama Bantul : Studi Kasus Tahun 2024 dan Tahun 2025 - Cahyati, Lutfiah; Sahril Fadli (International Forum of Researchers and Lecturers, 2026)
Inheritance disputes are among the most complex family disputes because they involve not only the distribution of inherited property but also emotional relationships and family values among heirs. This study aims to analyze the role of mediators in mediating inheritance disputes and the efforts undertaken by mediators to resolve inheritance disputes through mediation at the Bantul Religious Court in 2024 and 2025. This research employs an empirical normative legal research design with a qualitative and descriptive-analytical approach. Data were collected through interviews, observations, and documentation and subsequently analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings reveal that mediators play an essential role in all stages of mediation, namely the pre-mediation stage, the mediation process, and the post-mediation stage. Mediators act not only as communication facilitators but also as neutral parties in managing conflicts, building trust, and encouraging peaceful agreements among heirs. In addition, mediators employ persuasive approaches, provide an understanding of Islamic inheritance law, manage communication effectively, and utilize caucus techniques to overcome deadlocks during mediation. This study concludes that the success of inheritance dispute mediation is strongly influenced by the mediator's ability to manage legal, emotional, and social conflicts, thereby producing fair settlements and ensuring legal certainty for the disputing parties.